PENGARUH LAMA PENYIMPANAN TELUR HERBAL AYAM RAS FASE PERTAMA DI REFRIGERATOR TERHADAP PENURUNAN BERAT TELUR, DIAMETER RONGGA UDARA, DAN INDEKS ALBUMEN - Diana Widi Astuti; Khaira Nova; Rudy Sutrisna; Dian Septinova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to: (1) determine the effect of storage time of herbal eggs of chicken first phase in refrigerator temperature on egg weight loss, air cavity diameter, and albumen index, (2) determine the best storage time for herbal eggs of chicken first phase in refrigerator temperature (7,2oC) on egg weight loss, air cavity diameter, and albumen index. This research was conducted on October 7th – November 4th, 2020, at the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The material used were 60 eggs obtained from Sekuntum Herbal Farm with average weight of 56.67±3.21 g of first phase Lohmann strain chicken (30--40 weeks). The design used was a completely randomized design (CRD) with 5 treatments including storage time for 0, 1, 2, 3, 4 week and 4 replications. The variables observed were egg weight loss, air cavity diameter, and albumen index. The data obtained were analyzed based on Analysis of Variance at 5% significance level. The results that had a significant effect were further tested using the Least Significant Difference (LSD). The results showed that the storage time gave a significant effect (P<0.05) on egg weight loss, air cavity diameter, and albumen index of first phase chicken eggs. The storage time of herbal eggs for 1 week at refrigerator temperature showed better quality based on egg weight loss which was still low (1.14%), air cavity diameter (1.983cm), and albumen index (0.073). Key words: Herbal eggs, egg weight loss, air cavity, albumen index, refrigerator